Peningkatan Hasil Belajar Tematik Terpadu dengan Cooperative Learning Tipe Team Assisted Individualized di Sekolah Dasar - Oktriandi, Agung; Arwin, Arwin (Universitas Negeri Padang, 2021)
This study aims of study to illustrate an increase in student scores in integrated thematic learning used the TAI cooperative model in grade 5 elementary schools. This type of research is Classroom Action Research (PTK) used quantitative and qualitative approaches. The place of the research was carried out by the State Elementary School 27 Rawang, Pesisir Selatan Regency. The results of this study indicate: the assessment of the Learning Implementation Plan in cycle I 87.46% then increased in cycle II 97.22%, assessment of aspects of teachers and aspects of students in the first cycle was 85% then increased in the second cycle 97.5%, the assessment of attitudes in the first cycle was good, then in the second cycle it became very good, the assessment of the knowledge aspects for the first cycle obtained a value of 81 , 39 then increased in cycle II to a value of 95.06, the assessment of the skills aspect in cycle I obtained a value of 79.71 then increased in cycle II to 92.92.